Enhancing Qirā’ah and Fahm al-Nash Skills in Studying Safīnatun Najāh through the Ibtidai Method in Pesantren - Yulia Erviana (Journal Of Islamic Education And Pesantren, 2024)
This study aims to analyze the improvement of qirā’ah (reading ability) and fahm al-naṣṣ (textual comprehension) of Safinatun Najah through the application of the ibtidai method in Islamic boarding schools (pesantren). The ability to read and understand classical Islamic texts (kitab kuning) is a fundamental competence in the intellectual tradition of pesantren. However, students often encounter difficulties related to the mastery of Arabic grammatical structures and textual analysis. This research employed a qualitative approach with a case study design conducted at Ma’had Raudhotul Ulum Kras Kanigoro Kediri. Data were collected through classroom observations, interviews with teachers and students, and documentation of learning evaluation results. Data analysis was carried out using domain, taxonomic, and componential analysis to identify patterns of instructional implementation and their impact on students’ competencies. The findings reveal that the ibtidai method is implemented through a gradual instructional process consisting of reading nadzom to strengthen grammatical rules, the use of syntactic coding to facilitate sentence structure analysis, guided reading of vowelized texts, and sorogan practice in reading unvowelized classical texts. This instructional design forms a systematic scaffolding process that enables students to progressively read, analyze i‘rab, and comprehend the juridical meanings within Safinatun Najah. Evaluation results above the minimum competency standard indicate that the method effectively improves reading accuracy, grammatical analysis, and textual understanding.